The Relationship Of Smoking Behavior With Carboxyhemoglobin Levels In Active Smokers - Rica Vera Tarigan (Science Midwifery, 2021)
Smoking behavior is still entrenched in Indonesian cause a variety of diseases and even death. Cigarettes have become necessities of life that can not be abandoned in everyday life. The smoking problem in essence has become a national problem, even international level. But most connoisseurs of cigarettes assume that smoking is a personal responsibility for the consequences caused. Scientific researchers revealed that smoking is the leading cause of premature death. Statistical data shows that 90% of deaths due to respiratory problems, 25% of deaths caused by coronary heart disease that is triggered by smoking. In cigarette smoke contains 4000 chemicals, one of which is carbonmonoksida (CO), which can disturb binding of oxygen with hemoglobin (Hb), which transformed into bonds HbCO. This research used a correlational analysis with a quantitative approach and cross-sectional study design. Samples used as many 100 respondents used purposive sampling technique. Samples fill out the questionnaire and measured HbCO levels in the blood HbCO qualitatively. Data were analyzed with univariate, bivariate with Product Moment correlation techniques, multivariate correlation analysis. The results showed that there is a correlation of smoking behavior (number of cigarettes smoked by the respondent, the respondent smoking duration and type of cigarettes consumed by the respondents) against HbCO levels. Smoking behavior (knowledge, attitudes, and actions on how cigarette smoking cigarettes made by respondents) have no correlation with HbCO levels.